2019
DOI: 10.1111/echo.14562
|View full text |Cite
|
Sign up to set email alerts
|

Useful indices of thrombogenesis in the exclusion of intra‐cardiac thrombus

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Abstract Background: Cardioversion in patients with atrial fibrillation (AF) can cause cardioembolic stroke, and effective clinical management is necessary to reduce morbidity and mortality. Currently, transesophageal echocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
3
0
2
Order By: Relevance
“…On the other hand, reduced lymphocyte counts are an independent risk factor for poor prognosis in many diseases [ 32 35 ]. A prospective study by Ibebuogu et al found that peripheral blood lymphocyte levels were significantly lower in patients with D-dimer-positive thrombosis compared to those without thrombosis [ 20 ], suggesting a potential negative correlation between lymphocyte count levels and thrombosis. Firstly, reduced peripheral blood lymphocyte levels can cause immunosuppression and impaired regulation of the inflammatory response, leading to excessive or insufficient inflammatory response and promoting thrombosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, reduced lymphocyte counts are an independent risk factor for poor prognosis in many diseases [ 32 35 ]. A prospective study by Ibebuogu et al found that peripheral blood lymphocyte levels were significantly lower in patients with D-dimer-positive thrombosis compared to those without thrombosis [ 20 ], suggesting a potential negative correlation between lymphocyte count levels and thrombosis. Firstly, reduced peripheral blood lymphocyte levels can cause immunosuppression and impaired regulation of the inflammatory response, leading to excessive or insufficient inflammatory response and promoting thrombosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in patients with early-stage breast cancer, high LDL-C (> 3.6 mmol/L) increased the risk of catheter-related venous thrombosis by 2.36-fold [ 19 ]. On the other hand, lymphocytes play an important role in immunity and oxidative stress, and Ibebuogu et al have found a significant correlation between decreased lymphocyte levels and intracardiac thrombosis in atrial fibrillation [ 20 ]. However, it is inappropriate to extrapolate the above findings in patients with malignancy or cardiovascular disease to postoperative new-onset DVT in orthopedic or even OWHTO patients.…”
Section: Introductionmentioning
confidence: 99%
“…Дисфункция ЛЖ является независимым фактором риска развития тромбоза уЛП на фоне ФП, что подтверждено во многих исследованиях [52,53,77,78,90]. Степень дисфункции ЛЖ прямо влияет на повышение внутрипредсердного давления и ремоделирование ЛП [91].…”
Section: ____________________________________________________________...unclassified
“…Most of the thromboembolism in AF that causes ischemic stroke originates from the LAA[ 69 , 70 ]. Closure of the LAA represents a safe and effective strategy for stroke prevention, targeting patients with high bleeding risk[ 12 ], and a few clinical data support some devices for percutaneous LAAC.…”
Section: Introductionmentioning
confidence: 99%